Inference of photosynthetic capacity parameters from chlorophyll a fluorescence is affected by redox state of PSII reaction centers. (6th February 2022) - Han, Jimei; Gu, Lianhong; Wen, Jiaming; Sun, Ying
Abstract: Solar‐induced chlorophyll fluorescence (SIF) has been used to infer photosynthetic capacity parameters (e.g., the maximum carboxylation rate V cmax, and the maximum electron transport rate J max ). However, the precise mechanism and practical utility of such approach under dynamic environments remain unclear. We used the balance between the light and carbon reactions to derive theoretical equations relating chlorophyll a fluorescence (ChlF) emission and photosynthetic capacity parameters, and formulated testable hypotheses regarding the dynamic relationships between the true total ChlF emitted from PSII ( SIF PSII ) and V cmax and J max . We employed concurrent measurements of gas exchanges and ChlF parameters for 15 species from six biomes to test the formulated hypotheses across species, temperatures, and limitation state of carboxylation. Our results revealed that SIF PSII alone is incapable of informing the variations in V cmax and J max across species, even when SIF PSII is determined under the same environmental conditions. In contrast, the product of SIF PSII and the fraction of open PSII reactions q L, which indicates the redox state of PSII, is a strong predictor of both V cmax and J max, although their precise relationships vary somewhat with environmental conditions. Our findings suggest the redox state of PSII strongly influences the relationship between SIF PSII and V cmax and J max . Summary statement: Our theoretical and measurement results revealed that the fraction of open PSII reaction centers qL, which indicates the redox state of PSII plays an important role when chlorophyll afluorescence is used to infer V cmax25 and J max25 . The limitation state of carboxylation must be considered if observed chlorophylla fluorescenceis utilized to infer V cmax25 (or J max25 ) under dynamic environmental conditions.